Childhood violence exposure and social deprivation are linked to adolescent threat and reward neural function. Issue 11 (26th October 2020) - Hein, Tyler C; Goetschius, Leigh G; McLoyd, Vonnie C; Brooks-Gunn, Jeanne; McLanahan, Sara S; Mitchell, Colter; Lopez-Duran, Nestor L; Hyde, Luke W; Monk, Christopher S
Abstract: Background: Childhood adversity is, unfortunately, highly prevalent and strongly associated with later psychopathology. Recent theories posit that two dimensions of early adversity, threat and deprivation, have distinct effects on brain development. The current study evaluated whether violence exposure (threat) and social deprivation (deprivation) were associated with adolescent amygdala and ventral striatum activation, respectively, in a prospective, well-sampled, longitudinal cohort using a pre-registered, open science approach. Methods: One hundred and sixty-seven adolescents from the Fragile Families and Child Wellbeing Study completed functional magnetic resonance imaging (fMRI) scanning. Prospective longitudinal data from ages 3, 5 and 9 years were used to create indices of childhood violence exposure and social deprivation. We evaluated whether these dimensions were associated with adolescent brain function in response to threatening and rewarding faces. Results: Childhood violence exposure was associated with decreased amygdala habituation (i.e. more sustained activation) and activation to angry faces in adolescence, whereas childhood social deprivation was associated with decreased ventral striatum activation to happy faces in adolescence. These associations held when adjusting for the other dimension of adversity (e.g., adjusting for social deprivation when examining associations with violence exposure), the interaction of the two dimensions of adversity, gender, internalizing psychopathology, and current life stress. Conclusions: Consistent with recent theories, different forms of early adversity were associated with region-specific differences in brain activation.